1980
DOI: 10.1002/jmv.1890050305
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity liters of enterovirus as found in human stools

Abstract: Data have been gathered and collated from a variety of sources both published and unpublished, dealing with the concentration of enteroviruses in human stools. For polioviruses, a general range of 3.0-6.5 log10 TCD50 per gram of stool was reported, whereas for coxsackieviruses and echoviruses the range has been from 2.0-5.5 log10 TCD50. As human stools average about 100 gm, it is not unusual for an infected person to excrete as much as 10-300 million TCD50 of virus daily. The results of enterovirus titrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…These facts showed that this newly isolated virus, EHVF, possessed the typical characteri stics of herpesvirus previously described by Melnick (1980) and Roizman et al, (1981). Biochemical and molecular biological studies should be necessary to confirm this conclusion.…”
Section: Discussionsupporting
confidence: 79%
“…These facts showed that this newly isolated virus, EHVF, possessed the typical characteri stics of herpesvirus previously described by Melnick (1980) and Roizman et al, (1981). Biochemical and molecular biological studies should be necessary to confirm this conclusion.…”
Section: Discussionsupporting
confidence: 79%
“…Too little is known about the mode of poliovirus reproduction in the human gut to explain how consecutive random sampling from a heterogeneous viral population can be achieved in this case. A relatively low content of infectious virus in the feces (on the order 3.0 to 6.5 log 10 50% tissue culture infective doses/g [45]) makes it likely that either relatively few susceptible cells are available at each given moment or only a tiny minority of susceptible cells are effectively infected. If so, virus reproduction in the gut may be to some extent likened to the propagation of a virus by consecutive small-population passages, resulting in the accumulation of neutral and adverse mutations (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…Most EVs, excluding Enterovirus 70 (EV70) coxsackievirus A24 (CVA24) are abundant in stool specimens of infected individuals and levels of excretion of PVs are known to reach maximal amounts of 10 6 infectious virons per gram of feces (Dowdle et al, 2002;Hovi et al, 2007). Less information is available for levels of excretion of other enterovirus genotypes; however, the consensus from previous and current references indicates that humans excrete between 10 6 and 10 7 EVs per gram of feces (Feachem et al, 1983b;Gerba, 2000;Melnick and Rennick, 1980). The duration of intestinal virus shedding and thus the spreading (i.e., transmission) of a particular enterovirus may vary among the different genotypes.…”
Section: Reservoirs and Fecal Sheddingmentioning
confidence: 99%